Professional Identity Promoting Professional Development of Teachers in Forestry Science Based on Survival Analysis Model - Li Liqin (Forest Chemicals Review, 1970)
Survival analysis model is one of the common analysis models in forest industrialmanufacturing. Based on the survival analysis model, this paper studies the role of professionalidentity in promoting professional development of teachers in forestry science. Teachers withdifferent professional identity have different development characteristics in all aspects ofprofessional structure. On the basis of field interviews, this study analyzes four ways thatteachers' professional identity affects their professional development. The results show thatprofessional identity can stimulate the persistence of teachers' professional beliefs and promotethe reasonable construction of teachers' professional ideas; Professional identity can stimulateteachers' reflection and accumulation. Professional identity can promote the development ofteachers' professional knowledge and ability. Professional identity can stimulate the motivationof teachers' development and affect the formation and change of professional attitudemotivation. Professional identity can promote teachers' awareness of self professionaldevelopment and tend to the ideal state of professional development. The results of this studyhave a certain reference value for the research on the promotion of teachers' professionalidentity to professional development.